Polarization-dependent deformation in light responsive polymers doped by dichroic dyes. Issue 6 (4th December 2018) - Martella, Daniele; Nocentini, Sara; Micheletti, Filippo; Wiersma, Diederik S.; Parmeggiani, Camilla
Abstract : A polarization-dependence of the deformation in light-responsive materials can be induced through optimizing the dye dopant alignment. Abstract : Light represents a very versatile stimulus and its use to control the deformation in shape-changing polymers can take advantage of multiple parameters (such as wavelength, intensity and polarization) to be explored in order to obtain differentiated responses. Polymers with selected color responsiveness are commonly prepared by using different dyes, while a polarization-dependent control can be introduced exploiting trans – cis isomerization of azobenzenes. As shape-changing polymers driven by a photothermal effect are gaining more and more attention in many application fields, exploring polarization to modulate their response could enlarge the tuning parameter space and provide an insight into the material optical properties. In this work, we demonstrate the effect of light polarization on the deformation of liquid crystalline networks doped by a small amount of a push–pull azobenzene. We demonstrate how enhancing the dye alignment in the polymeric matrix leads to different deformations by orthogonal polarizations. These results demonstrate polarization as a convenient further degree of freedom besides wavelength and intensity of the light stimulus.